Pengaruh Tata Kelola Perusahaan, Tanggung Jawab Sosial Perusahaan, dan Ukuran Perusahaan Terhadap Kinerja Perusahaan Sektor Perbankan - Safitri, Aulia Fadira; Ramadhan, Yanuar (MES Management Journal, 2026)
This study is useful for determining the influence of Corporate Governance, Corporate Social Responsibility, and Company Size on Company Performance in the banking sector listed on the IDX in 2020-2023. The data source used in this research is secondary data with a population of 47 banking companies, so that the results of the research sample from the purposive sampling method were 60 data from 15 companies over a period of 4 years. The method used is Quantitative with Multiple Linear Regression analysis test using statistical testing software. This study provides results that Company Size Have a Positive Influence on Company Performance. However, Independent Commissioners, Audit Committee Meetings, Managerial Ownership and Corporate Social Responsibility have no influence on Company Performance. The findings of this study can be an evaluation for investors to be more careful in receiving signals in the form of information about the company's condition before making a decision to invest. For companies, it can be a reference to continue to practice good governance so that it has an impact on the sustainability of the company in the long term.